Synthesis, Crystal Structure, and Infrared Spectroscopy of a novel hydronium trihydrate hybrid compound: (C6H22N4)2H9O4CdCl6CdCl5Cl2 - Glaoui, Maroua El; MI, Jin-Xiao; Pereira da Silva, Pedro Sidonio; Lefebvre, Frédéric; Silva, Manuela Ramos; Nasr, Chérif Ben (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A 0-dimensional (0D) hybrid compound, (C6H22N4)2H9O4CdCl6CdCl5Cl2 has been prepared by a facile conventional evaporation method. The crystal packing of discrete constituents of [Cd(1)Cl6] octahedra, [Cd(2)Cl5] trigonal bipyramids, Cl– ions, protonated tris(2-aminoethyl)amine molecules ([(C2H7N)3NH]4+) and H9O4+ ions, is stabilized by diverse hydrogen bonds of N-H···Cl, C-H···Cl and C-H···O. Uncommonly, an isolated chlorine ion (i.e. Cl(4)) is fixed at a special position at 12c(3.) by hydrogen bonds from four surrounding hydrogen atoms at a trigonal pyramidal configuration whereas other chlorine atoms Cl(1), Cl(2) and Cl(3) are stabilized by hydrogen bonds from 2, 2 and 3 hydrogen atoms at bifurcated, linear and trigonal configurations, respectively. The ordered arrangement of [Cl(4) [Cl(4)···H4] trigonal pyramidal configuration upward or downward is responsible for the long c-axis of the title compound. Additionally, a H9O4+ ion is entangled with symmetry restriction and half occupancy. All these features of the title compound add our new knowledge about hydrogen bonds.